2018
DOI: 10.1111/jch.13141
|View full text |Cite
|
Sign up to set email alerts
|

Measure Accurately, Act Rapidly, and Partner With Patients (MAP) improves hypertension control in medically underserved patients: Care Coordination Institute and American Medical Association Hypertension Control Project Pilot Study results

Abstract: Measure Accurately, Act Rapidly, and Partner With Patients (MAP) is an evidence‐based protocol implemented to improve hypertension control in a clinic for underserved patients (49.9% Medicaid and 50.2% black). Patients with hypertension seen during the year before intervention and with at least one visit during the 6‐month intervention (N = 714) were included. If initial attended blood pressure (BP; standard aneroid manometer) was ≥140/≥90 mm Hg, unattended automated office BP was measured in triplicate and av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
0
35
1
2
Order By: Relevance
“…[28] More recently, the AMA has collaborated with the Care Coordination Institute. [29] and the American Heart Association in Target: BP. [26] The changes in the primary outcomes measured dur-ing the IHO: BP pilot may not reflect the potential impact of the program, but these efforts continue to offer valuable insights to the IHO: BP project team on how best to engage physicians and care teams across the nation in the effort to improve blood pressure control and reduce the risks of heart attack and strokes.…”
Section: Resultsmentioning
confidence: 99%
“…[28] More recently, the AMA has collaborated with the Care Coordination Institute. [29] and the American Heart Association in Target: BP. [26] The changes in the primary outcomes measured dur-ing the IHO: BP pilot may not reflect the potential impact of the program, but these efforts continue to offer valuable insights to the IHO: BP project team on how best to engage physicians and care teams across the nation in the effort to improve blood pressure control and reduce the risks of heart attack and strokes.…”
Section: Resultsmentioning
confidence: 99%
“…Our MAP study in 16 Family Medicine clinics confirmed a clinically and statistically significant improvement in BP as reported in our pilot study. 13 Hypertension control increased from 64.4% to 74.3% ( P <0.0001) in 16 787 hypertensive adults in only 6 months (Figure). Absolute hypertension control rates improved 9.9% although the increase was smaller than the absolute increase of 28.6% in our single site pilot.…”
Section: Discussionmentioning
confidence: 93%
“…Absolute hypertension control rates improved 9.9% although the increase was smaller than the absolute increase of 28.6% in our single site pilot. 13 Implementing the project across multiple sites yielded significant but less dramatic changes than the pilot study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on implicit bias given the evidence of its impact on interpersonal communication 7 and patient outcomes, 2,5 particularly in hypertension where it contributes to a complex interaction of suboptimal clinical decision making and unsatisfactory patient experience of care. 18 (Figure 1)…”
Section: Core Educational Elementsmentioning
confidence: 99%